(untitled) (American Journal of Islam and Society, 2005)
Multicultural Politics: Racism, Ethnicity, and Muslims in Britain is an eloquent analysis of empirical and theoretical observations of multiculturalism in Britain. Modood is an expert on this topic, in particular as he writes from a Muslim perspective. The book consists of two parts: “Racism, Disadvantage, and Upward Mobility,” which discusses ethnic diversity in employment and educational performance, and “The Muslim Challenge,” which comprises chapters five to nine. The book’s main purpose is to critique the British perception, which the author labels a “black-white dualism” (p. 5), and the resultant ignorance surrounding the voices of Asians and other minorities. Modood argues that the black-white division is complicated by cultural racism, Islamphobia, and a challenge to secular modernity. In his introduction, the author sets the stage by providing a brief autobiographical background of how he embarked on the topic of multicultural politics from a philosophical background. These background details are not “nostalgic self-indulgence … in fact, some of the book’s themes are rooted in descriptions from childhood” (p. 4). Throughout the book, Modood emphasizes the “otherness” of Asians, particularly South Asians in Britain, as it existed before the tragedy of September 11 and subsequent terrorist attacks. He argues that in the pluralist nation of Britain, “South Asians were treated as [the] undesirable other” (p. 5). Muslims, not blacks, were increasingly perceived as the most threatening “other” to Western society. He further argues that race and racism are intricately entangled in how British Muslims were perceived, and that their culture was habitually stereotyped and perceived as obstructive to assimilation and integration into British society. The author’s arguments shed light on how British Asians are empirically subjected to double racism, as compared to British blacks. Modood acknowledges that this complex situation has to be considered along with such other variables as “class, gender, geography, and [the] social arena” (p. 7) ...